Species and Density of Limpets (Patellogastropoda) in The Intertidal Rocky Shore Akaiwa - Poluan, Irene; Rumengan, Inneke F.M.; Paruntu, Carolus P.; Bara, Robert A.; Sumilat, Deiske A.; Boneka, Farnis B. (JURNAL PESISIR DAN LAUT TROPIS, 2026)
Rocky intertidal shores are dynamic coastal ecosystems characterized by strong environmental gradients that generate distinct patterns of organism zonation. Limpets (Patellogastropoda) play a crucial role as primary herbivores and ecological indicators in these habitats. This study aimed to examine species composition and density of limpets in the upper and lower intertidal zones of the rocky intertidal shore of Akaiwa, Tomioka, Amakusa, Japan. The research was conducted from February to March 2025. Sampling was conducted using a quadrat sampling method with quadrats measuring 25 cm × 25 cm, randomly placed within a 10 m × 15 m study area across the upper and lower intertidal zones. Limpet specimens were identified based on shell morphological characteristics, and species density was calculated and statistically compared between zones using a t-student test. The results recorded eight limpet species belonging to the families Lottidae and Nacellidae, with seven species occurring in the upper zone and six species in the lower zone. Limpet density in the upper intertidal zone ranged from 1.60 to 20.80 ind/m² and was dominated by Lottia tenuisculpta, whereas the lower zone exhibited higher densities ranging from 1.60 to 28.80 ind/m², with a significant dominance of Cellana toreuma. The study concludes that limpet community structure is strongly influenced by vertical intertidal zonation. Further long-term studies are recommended to elucidate temporal dynamics of limpet communities in relation to seasonal variation and environmental change. Keywords: Amakusa, density, limpet, Akaiwa rocky shore, intertidal zonation   Abstrak Pantai intertidal berbatu merupakan ekosistem pesisir yang dinamis dengan gradien lingkungan yang kuat, sehingga membentuk pola zonasi organisme yang khas. Limpet (Patellogastropoda) berperan penting sebagai herbivora utama dan indikator ekologis pada ekosistem ini. Penelitian ini bertujuan untuk mengkaji komposisi jenis dan kepadatan limpet pada zona atas dan zona bawah pantai rocky intertidal Akaiwa, Tomioka, Amakusa, Jepang. Penelitian ini dilaksanakan pada Februari-Maret 2025. Pengambilan sampel dilakukan dengan metode quadrat sampling menggunakan kuadrat berukuran 25 cm × 25 cm yang ditempatkan secara acak di area 10 m × 15 m pada zonasi intertidal bagian atas dan bawah. Spesimen limpet diidentifikasi berdasarkan karakter morfologi cangkang, kemudian dianalisis kepadatan jenis dan diuji perbedaannya antar zona menggunakan uji t-student. Hasil penelitian menunjukkan bahwa delapan spesies limpet dari famili Lottidae dan Nacellidae teridentifikasi, dengan tujuh spesies pada zona atas dan enam spesies pada zona bawah. Kepadatan limpet di zona atas berkisar antara 1,60-20,80 ind/m² dan didominasi oleh Lottia tenuisculpta, sedangkan zona bawah memiliki kepadatan lebih tinggi, yaitu 1,60-28,80 ind/m², dengan dominasi Cellana toreuma yang berbeda nyata secara statistik. Kesimpulan penelitian menunjukkan bahwa struktur komunitas limpet dipengaruhi kuat oleh zonasi vertikal intertidal. Disarankan penelitian lanjutan dilakukan secara temporal untuk memahami dinamika komunitas limpet terhadap variasi musim dan perubahan lingkungan. Kata kunci: Amakusa, kepadatan, limpet, pantai berbatu Akaiwa, zonasi intertidal